Sensitivity Analysis of Product Price Decrease and Variable Cost Increase in Broiler Chicken Farming Business (Case Study at PT New Hop in Mandapa Village, Dawuan District, Majalengka Regency) - Harits, Abdul; Alghifary, Muhammad Ghaazi; Fikri, Muhammad Bayu; Wachdijono, Wachdijono (Ridwan Institute, 2025)
This study conducts a sensitivity analysis on price decreases and variable cost increases in the broiler chicken farming sector, specifically focusing on PT New Hop in Mandapa Village, Dawuan District, Majalengka Regency. The objective of this research is to assess the impact of economic fluctuations on business profitability and sustainability within the broiler farming industry. Utilizing the Break-Even Point (BEP) method, the study identifies the critical variables that influence revenue and profitability, offering strategic recommendations for farmers in managing these factors. The findings show that the broiler farming business can tolerate a 14.75% decrease in selling prices and a 17.70% increase in variable costs without incurring losses, highlighting the business’s resilience to certain economic changes. The results of this study provide valuable insights into risk management strategies for agribusinesses, emphasizing the importance of managing costs and pricing effectively to maintain profitability. Additionally, the research offers practical recommendations for improving operational efficiency in response to market fluctuations, which could support the long-term sustainability of broiler farming businesses. This study contributes to a broader understanding of how agricultural enterprises can mitigate financial risks and adapt to volatile market conditions.